Cover Image, Volume 8, Issue 2. (5th February 2021) - Kattel, Giri; Reeves, Jessica; Western, Andrew; Zhang, Wenjing; Jing, Wei; McGowan, Suzanne; Cuo, Lan; Scales, Peter; Dowling, Kim; He, Qiang; Wang, Lei; Capon, Samantha; et al.
Abstract: The cover image is based on the Focus Article Healthy waterways and ecologically sustainable cities in Beijing‐Tianjin‐Hebei urban agglomeration (northern China): Challenges and future directions by Giri Kattel et al., https://doi.org/10.1002/wat2.1500 . Abstract : The cover image is based on the Focus Article Healthy waterways and ecologically sustainable cities in Beijing‐Tianjin‐Hebei urban agglomeration (northern China): Challenges and future directions by Giri Kattel et al., https://doi.org/10.1002/wat2.1500 .